Influence of Fermentation Time on Total Lactic Acid Bacteria, pH Value, Water Activity, and Organoleptic Properties of Mutton Jerky - Dwiloka, Bambang; Rizqiati, Heni; Susanti, Siti; Kamil, Rafli Zulfa; Mulyani, Sri; Susanto, Farrel Ihza Noer (Diponegoro University, 2024)
Mutton is a type of meat that is rarely consumed by the public because it has a high saturated fat content. Mutton has good quality and characteristics and can be used as a functional product to improve body health by adding probiotic bacterial cultures. Mutton jerky can be an alternative to functional meat products. Mutton jerky is fermented utilizing a probiotic starter Lactobacillus plantarum for 6 hours (T1), 12 hours (T2), 18 hours (T3), and 24 hours (T4). The fermented mutton jerky is then dried in a cabinet for 8 hours and then examine. Total lactic acid bacteria was examined by dilution, pH value by pH meter, water activity by aw meter, and organoleptic properties by sensory test. The data of total lactic acid bacteria were analyzed descriptively. The data of pH value and water activity is processed with the ANOVA test and the nonparametric test with the Kruskal Wallis method. The result of this research show fermentation time on lowering the pH value and water activity. At the same time, the total lactic acid bacteria experienced a decrease in value which was analyzed descriptively. The conclusion of this research is that the longer the fermentation will cause a decrease in total LAB, pH value, and water activity and affect the panelist's assessment of the organoleptic test. Mutton jerky with the addition of L. plantarum bacterial starter, which was fermented for 18 hours, had the best treatment to produce low pH values and water activity.